Biodiversity and Wind Farms in Portugal Current knowledge and insights for an integrated impact assessment process (Springer International Publishing, 2018)
This book presents a review of the state-of-the-art knowledge on the interactions between biodiversity and wind energy development, focused on the Portuguese reality. The volume addresses the particularities of the impact assessment procedures in Portugal, contrasting it with the international practices and presenting its main findings by covering the following broader themes: i) evaluation of spatial and temporal dynamics of wildlife affected by wind farms, including birds, bats and terrestrial mammals (in particularly Portuguese wolf population); ii) the methodologies used to assess impacts caused by this type of developments in biodiversity; iii) the best practice methodologies to implement an adaptive management approach to reconcile biodiversity and wind farms. The knowledge presented in this book was gathered through the research and development activities developed by Bioinsight company (former Bio3 company) during the last 13 years and partially funded by a R&D project designated as "Integrated solutions for biodiversity management at wind farms: reduce and compensate bird and bat mortality" (acronym: Wind & Biodiversity), co-funded by the European Regional Development Fund (FEDER), under the Regional Operational Programme of Centre (Mais Centro). This volume fills a void in the literature as a book giving insights on the best practices to install and manage a wind farm from a biodiversity management point of view, while establishing a commitment between economic sustainability and biodiversity conservation.